2015
DOI: 10.1159/000369720
|View full text |Cite
|
Sign up to set email alerts
|

APRIL Induces Cisplatin Resistance in Gastric Cancer Cells via Activation of the NF-κB Pathway

Abstract: Background: A proliferation-inducing ligand (APRIL) is a tumor-necrosis factor (TNF) family member and is a novel cytokine crucial in sustaining lymphocytic leukemia B cell survival and proliferation. However, its role in gastric cancer (GC) remains unclear. In this study, we investigated the expression pattern and prognostic role of APRIL in GC. Methods: Expression of APRIL was assessed by immunohistochemistry and real-time PCR. Prognostic role of APRIL expression was evaluated. We also discovered the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Although APRIL has low or no expression in various normal cells, previous studies have shown that it is overexpressed in many malignancies, such as colorectal cancer [13], pancreatic cancer [26], and gastric cancer [27], suggesting that APRIL plays an important role in the carcinogenesis of these tumors. Moreover, APRIL also owns an ability to stimulate tumor cell proliferation and survival in vitro and in vivo by interaction with the intracellular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although APRIL has low or no expression in various normal cells, previous studies have shown that it is overexpressed in many malignancies, such as colorectal cancer [13], pancreatic cancer [26], and gastric cancer [27], suggesting that APRIL plays an important role in the carcinogenesis of these tumors. Moreover, APRIL also owns an ability to stimulate tumor cell proliferation and survival in vitro and in vivo by interaction with the intracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it may enable deeper insight into the regulation of gene expression and the potential complexity in HCC. Besides, although it was reported that APRIL could promote tumor progression via, for example, TGF-β1/ERK, PI3K/Akt, and NF-κB signaling pathways [13,27,31], further studies are also needed to elucidate the specific mechanisms of miR-383-APRIL axis in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that APRIL could upregulate the activity of nuclear factor NF-κB (22). Therefore, we speculated that APRIL knockdown and/or JXY treatment may downregulate the activity of nuclear factor NF-κB directly.…”
Section: Resultsmentioning
confidence: 99%
“…DDP, a chemotherapy drug commonly used to treat gastric cancer [2022] acts by inducing mitochondrial apoptosis in cancer cells; however, drug-resistant gastric cancer cells are not sensitive to this agent, and thus, considerable attention has been placed on this issue [23, 24]. Studies have indicated that TCM combination with chemotherapy for cancer can enhance the efficacy of and diminish the side effects and complications caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%